Comparison of the Effects of Different Decontamination Methods on Staphylococcus Aureus Biofilm - Ece Açıkgöz Alparslan; Ufuk Bağcı; Ayşegül Kurt (European Annals of Dental Sciences)

(untitled)
Purpose: The current in-vitro study aims to compare the effectiveness of various mechanical decontamination modalities in the elimination of Staphylococcus aureus biofilm from titanium surfaces using qualitative and quantitative techniques.Materials and methods: A total of 48 titanium discs were inoculated with Staphylococcus aureus and randomly allocated into four experimental groups consisting of control, plastic curettes (PC), ultrasonic-driven plastic tips (UPT), and ultrasonic-driven stainless-steel tips (UST). Following decontamination procedures, colony-forming units and viable biomass were analyzed to identify the biofilm removal efficacy of the treatments and the viability of bacteria remaining on the surface. Biofilm structure was assessed by confocal laser scanning microscopy and scanning electron microscopy. Analysis of variance and post hoc Tukey tests were applied for comparisons.Results: Reductions in both colony counts and variable biomass following the decontamination procedure were significant in all treatment groups (p=0,000). Although the highest reduction in colony count was determined in the UST and the lowest in the PC group, the difference was not statistically significant between treatment groups (p = 0.246). Nonetheless, the reduction in viable biomass in the UST group was greater than in the UPT and PC groups (p=0.005, p=0.000, respectively).Conclusion: Ultrasonic-driven instruments are more effective than plastic curettes in removing the biofilm that colonizes the titanium surfaces in the initial stages. Stainless steel tips provide better elimination of microbial biofilm compared to plastic instruments, but they alter the surface topography of roughed titanium surfaces more than plastic curettes.